The Effect of Work Attachment, Emotional Intelligence, and Work Fatigue on Turnover Intention At PT. X - Sukmawati, Enah; Kartono, Kartono (Jurnal Ekuisci, 2026)
Background. The garment industry needs to be resilient and sustainable, requiring both physical resilience and adaptability. The stability of the technology has become a key factor in maintaining the company's smooth production, so the problem of turnover has become a challenge. Turnover is often found in the garment sector, including in the textile section. Purpose. This study aims to analyze the influence of work attachment, emotional intelligence, and work fatigue on employee turnover intention at PT. X. Method. The study used a quantitative approach with the Structural Equation Modeling method based on Partial Least Squares (SEM-PLS) to test the causal relationship between variables. The research population is all employees of PT. X as many as 2,452 people, with a sample of 344 respondents selected through a simple random sampling technique. Data were collected using a Likert-scale questionnaire and analyzed with SmartPLS 4.0. Results. The results showed that work attachment had a negative and significant effect on turnover intention (β = –0.208; p < 0.05), emotional intelligence had a negative and significant effect (β = –0.171; p < 0.05), and work fatigue had a positive and significant effect (β = 0.556; p < 0.05). Simultaneously, all three variables explained 68.9% of the variation in turnover intention (R² = 0.689), suggesting that the research model is relatively robust. Conclusion. These findings indicate that work attachment and emotional intelligence serve as protective factors in suppressing employee exit intentions, while work fatigue is the dominant factor that increases turnover intentions. Implementation. Therefore, companies are advised to increase work attachment, develop emotional intelligence, and manage workloads effectively to maintain employee stability and retention.